Long-term and short-term stability characteristics of receiver inter system bias for BDS3/BDS2 - Jingxuan Guo; Weiping Jiang; Yan Chen; Xincheng Ma; Hua Chen (Geodesy and Geodynamics, 2023)
The study of inter-system bias (ISB) is important for multi-system fusion and the performance of different signal compatibility. In this paper, the stability of ISB at the BDS3/BDS2 receiver end is calculated and analyzed for different time spans (DOY 060∼090 in 2021) from a total of 31 MGEX and iGMAS stations. We adopted two estimation strategies, random walk and constant approach, using the precision products of orbit and clock bias provided by WUM, the influence of which on ISB was also analyzed. Our results showed that the ISB value varied little within a day, and the mean of daily ISB standard deviation was only 0.037 m when the observation condition was good. The signal reception was continuous, indicating a high ISB stability for one day. If extending the time series to one month, however, the ISB standard deviation calculated by constant approach, in which a constant ISB is estimated on a daily basis was about 0.1 m, and the results of adjacent days were not continuous, with no apparent pattern. Concerning the random walk approach, the obtained ISB time series also had a jump, and the conclusion was the same as that of the constant strategy. Besides, receiver types showed a strong regularity in ISB numerical situation, and the distribution of ISB values corresponding to the same receiver type was relatively close. Therefore, we conclude that the ISB parameters remain stable in the short term (one day) and less stable in the long-term period. It is recommended that the ISB term should be set as a constant estimate every day in BDS3/BDS2 solutions, regardless of receiver type consistency.